-36+8x=2(2+8x)

Simple and best practice solution for -36+8x=2(2+8x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -36+8x=2(2+8x) equation:


Simplifying
-36 + 8x = 2(2 + 8x)
-36 + 8x = (2 * 2 + 8x * 2)
-36 + 8x = (4 + 16x)

Solving
-36 + 8x = 4 + 16x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-16x' to each side of the equation.
-36 + 8x + -16x = 4 + 16x + -16x

Combine like terms: 8x + -16x = -8x
-36 + -8x = 4 + 16x + -16x

Combine like terms: 16x + -16x = 0
-36 + -8x = 4 + 0
-36 + -8x = 4

Add '36' to each side of the equation.
-36 + 36 + -8x = 4 + 36

Combine like terms: -36 + 36 = 0
0 + -8x = 4 + 36
-8x = 4 + 36

Combine like terms: 4 + 36 = 40
-8x = 40

Divide each side by '-8'.
x = -5

Simplifying
x = -5

See similar equations:

| 4u+16=7u+1 | | 35y^2-2y+2= | | x^2+15x^2= | | 3b^2+12b+12=0 | | 9+21y= | | 21y+10=28 | | 35=4x+15 | | 150+(3x-15)=180 | | 4n-6=8 | | X+2Y+21=0 | | 8+2=30 | | 4y=y+33 | | 0=x^2+6x+17 | | -4(8x+43)-18x=4x-13(2-18) | | 2(y+2)=12 | | 0=2x^2-16x+38 | | 36=.5(x*2x) | | 44=2(3w+w) | | x^3-5x^2+3x-5x-6= | | 9+x=93 | | 2.4=x+3.7 | | 4(d+6)= | | 890/2 | | -3x^3+10x^2-3x=0 | | 5(2c+3)-8=3(4c+2)-2c | | 0.5x-0.3(50+x)=0.3(50) | | 6+7x=4x+1 | | 27=x3/2 | | 5(4-6x)=8+6(7+2x) | | 4^2/2=3y | | 2(7b-4)=b-21 | | 5x+8+7x+10=90 |

Equations solver categories